(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2025)
In a context of disruptive changes, it is said that we live in a kind of attention economy, a new and different business model, characterized by a concept where attention is valuable, because it means money, since it translates directly into an economy of time. Thus, companies, under the pretext of free use, “privacy” and “security”, often biased and illegal, capture personal data of users, either through social networks, videos, applications, games, thereby making a study-analysis of their profiles and using these to offer products and / or personalized services. Thus, the multiple applications derive in multiple distractions, which often become a prison without bars, because they make us unconscious/vulnerable, depriving us of the freedom to think autonomously, transforming us into consumer robots. This, without counting the direct violations of privacy through data manipulation. And all this for money in exchange for attention. Is this fair or not?